Lymphocytic Variant of Triple-Negative Breast Cancer Carcinoma Erysipeloides: A Rare Case of Carcinoma Erysipeloides Following TNBC Mastectomy: Breast Carcinoma with unusual visitor in PBS - Ahmed, Amr; Akl, Maher (Archives of Breast Cancer, 2024)
Background: Carcinoma erysipeloides (CE) is a rare but significant cutaneous manifestation of metastatic breast cancer, often misdiagnosed due to its rarity and nonspecific presentation. This is particularly true in patients with triple-negative breast cancer (TNBC), where the disease may progress undetected by conventional imaging modalities. This manuscript aims to elucidate the challenges and implications of diagnosing CE in breast cancer survivors, emphasizing the insufficiency of PET scans in detecting such cutaneous metastases and the potential for mismanagement due to diagnostic oversight. Case Presentation: We present a detailed case study of a 43-year-old female with a history of metastatic TNBC, who developed suspicious skin lesions post-treatment. Despite initial negative PET scan results, further investigations revealed CE through histopathological examination of skin biopsies. The case highlights the critical need for biopsy in the presence of new skin lesions in breast cancer survivors, irrespective of imaging results. It also underscores the possibility of lymphatic spread of CE, which could lead to life-threatening complications if not properly managed. Conclusion: The diagnosis of carcinoma erysipeloides must be considered in patients with breast cancer presenting with unusual skin lesions. Increased vigilance and dermatological assessment should be integral to the post-cancer follow-up regimen. The findings advocate for revising current treatment protocols and guidelines to better manage and potentially prevent the complications associated with this diagnosis. Enhanced surveillance for dermatological changes and a more aggressive approach to the biopsy of new skin lesions in cancer patients are recommended to improve outcomes and prevent the misdiagnosis of CE.